Phytoremediation of electroplating wastewater by vetiver grass (Chrysopogon zizanoides L.) - Andhika Puspito Nugroho (Nature Portfolio, 2021)
Abstract The electroplating industry generates wastewater containing a variety of heavy metals which potentially contaminate water ecosystems. The available and well-known electroplating wastewater treatments are considered as an expensive and less effective method, therefore phytoremediation was used as an alternative friendly solution. This study aims to evaluate the uptake and elimination rate of heavy metals by vetiver (Chrysopogon zizanoides L.) on metal-polluted water. Vetiver was planted in artificial electroplating wastewater containing different levels (low, medium, high) of chromium (Cr) and nickel (Ni). Water, roots, and shoots were collected periodically to determine Cr and Ni contents using Atomic Absorption Spectrometry (AAS). Metal accumulation and elimination rate, Bioconcentration Factor (BCF), Biological Absorption Coefficient (BAC), and Translocation Factor (TF) were calculated to evaluate plant’s effectiveness in metal remediation processes. The results showed that vetiver (C. zizanoides L.) was able to remove 61.10% Cr and 95.65% Ni on metal-contaminated water. The highest uptake rates for Cr and Ni are 127.21 mg/kg/day and 15.60 mg/kg/day respectively, while the elimination rates for Cr and Ni tend to slow 1.09 mg/kg/day and 12.24 mg/kg/day respectively. Vetiver BCF, BAC, and TF values on Cr and Ni contaminated water were greater than 1, which indicates that vetiver work through phytoextraction and phytostabilization to treat metals. The findings showed that vetiver has promise as a phytoremediation agent thus providing implication for electroplating wastewater treatment.